Flame retardancy and toughening properties of epoxy composites containing ammonium polyphosphate microcapsules and expanded graphite. (December 2018) - He, Da; Zhao, Chunxia; Gou, Haolan; Li, Yuntao; Xiang, Dong
Ammonium polyphosphate microcapsules (BM (polybenzoxazine modified) APP) were prepared through the in situ ring-opening polymerization of allyl group containing benzoxazine monomers on the surfaces of ammonium polyphosphate (APP), and they were significantly hydrophobic than the APP. A flame retardant system of epoxy (EP) resin was prepared with BMAPP and expanded graphite (EG). Flame retardancy, the thermal degradation behavior, a mechanical property of EP and EP/BMAPP/EG composites was investigated through limited oxygen index, vertical burning test, cone calorimetry (CONE), and the thermogravimetric analysis (TGA). The flame retardancy tests indicated that the EG could improve the thermal performance, promote the charring, and enhance the char quality of EP/BMAPP. Scanning electron microscopy (SEM) and Fourier-transform infrared spectroscopy (FTIR) were employed to analyze the morphology and composition of the char residue formed during CONE testing, and to understand the mechanism of char formation. The results of TG-FTIR confirmed the possible mechanism of flame retardancy of EP/BMAPP/EG in the gas phase during combustion. The EG content effects on Young's modulus, the tensile strength, and the fracture toughness ( K IC ) of the EP/BMAPP composites were also investigated. The K IC of the composites containing 1% of EG and 10% of BMAPP increased by approximately 76% and 153%, respectively, compared to the neat matrix and EP/BMAPP-10%. The SEM images of the fractured surface indicated that the enhanced toughness of EP/BMAPP/EG composites mainly attributed to the debonding of the BMAPP and the subsequent plastic void growth of the matrix, as well as the crack deflection effect of the BMAPP/EG.